Evapotranspiration prediction using system identification and genetic algorithm - Robiah, Ahmad, Dr.; Saiful Farhan, Mohd Samsuri; Mohd Zakimi, Zakaria (Acta Press, 2012)
Link to publisher's homepage at http://www.actapress.com/